Determinants of Transfer of Training: A Comprehensive Literature Review - Tonhäuser, Cornelia; Büker, Laura (International Journal for Research in Vocational Education and Training, 2016)
Investments in training measures can only be considered effective if the transfer of the learned contents to practical situations is continuously successful. In this context the scientific and professional discourse regarding the effectiveness of further education, especially regarding training transfer, has intensified considerably. This analysis provides a systematic and comprehensive overview of the current state of international empirical research regarding major influencing factors of learning transfer in the context of formalized further vocational training. Our review of literature differentiates the most important influencing factors on the micro-level of the specific individual characteristics of the participants, the meso-level of measure-specific characteristics of the field of learning, as well as institutional characteristics of the work environment at the macro-level. Decades of transfer research brings forth a wealth of information regarding factors which influence the learning transfer. The current analysis systematizes these results and clarifies that the current state of research regarding the determinants of the process of learning transfer shows clear trends. But there are also some inconsistent findings. Thus the question of which factors positively influence the success of learning transfer is well-studied for the micro-level in particular. The article shows that there is still a research deficit concerning the major determinants of learning transfer at the meso- and macro-level. Finally, in this context this article identifies promising directions for future research.